INTEGRASI HIMPUNAN DAN HADIST SERTA IMPLEMENTASINYA DALAM PEMBELAJARAN MATEMATIKA DENGAN PRINSIP TAUHID ISLAM - nabila, maesa; Winda Dwi Agustin; Jarilla Syahdita Azza N. A. A. S; Aci Via Ferlin Fertika; Mohammad Kholil (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
This study aims to explore the integration of the set theory concept in mathematics with Islamic values found in hadiths, as well as its implementation in teaching based on the principle of tawhid (Islamic monotheism). Using a literature review method and a thematic analysis approach, this research identifies the connections between set theory concepts—such as the universal set, subsets, and set relations—and Islamic principles like tawhid, Islamic brotherhood (ukhuwah Islamiyah), and the classification of people based on faith as reflected in authentic hadiths. The findings reveal that these mathematical concepts can be analogized to Islamic teachings, thus providing a spiritual dimension to mathematics learning. The integration approach is expected to enhance students' conceptual understanding while also shaping their character in accordance with Islamic values. This study recommends developing mathematics learning strategies grounded in religious values to strengthen the relationship between science and Islamic teachings.